2016
DOI: 10.17795/ijcp-4618
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Capital Enhancement on Quality of Life, Treatment Compliance and Pain in Patients with Breast Cancer

Abstract: Background: Nowadays, research about quality of life in breast cancer patients is so important, because of progress in treatment procedure in health science. Brest cancer influences quality of life aspects and disrupts social relationships. This creates recluse lifestyle and speeds up disease trend. Objectives: The aim of this study was to investigate the effect(s) of social capital on quality of life, treatment compliance, and pain in patients with breast cancer. Materials and Methods:In a clinical trial, 29 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
(14 reference statements)
1
7
0
Order By: Relevance
“…The result of the study is in line with Hosseini et al (2016) who conveyed that social capital has positive correlation toward breast cancer survivors' quality of life. High social capital will improve patients' quality of life and reduce patients' pains.…”
Section: The Effect Of Social Capital Toward Breast Cancer Survivors' Quality Of Lifesupporting
confidence: 85%
“…The result of the study is in line with Hosseini et al (2016) who conveyed that social capital has positive correlation toward breast cancer survivors' quality of life. High social capital will improve patients' quality of life and reduce patients' pains.…”
Section: The Effect Of Social Capital Toward Breast Cancer Survivors' Quality Of Lifesupporting
confidence: 85%
“…The results suggested a positive and significant correlation between social capital and the physical (0.24) and mental health dimensions (0.26) of QoL. Although the association between QoL and social capital in pregnant women had not previously been studied, positive and significant associations have been reported between social capital and QoL (as well as other aspects of health in other age and social groups) [6, 8, 2831]. For example, in a study by Rajabi et al (2013), the Pearson correlation coefficient between the total social capital of teachers (both male and female)—including the physical and mental components of QoL—was 0.14 [17].…”
Section: Discussionmentioning
confidence: 99%
“…Psychological hardiness as an internal resistance resource reduces the detrimental effects of stress and prevents the improvement of physical and psychological disorders [14]. Kakpour and Teymouri found that hardy women are more likely to attend treatment sessions than others [25,26]. The people with high psychological hardiness compared with those who have lower psychological hardiness are less likely to be physically or mentally damaged in response to life pressures.…”
Section: Discussionmentioning
confidence: 99%